The Relationship Between Meaningful Physical Education and Students' Self-Efficacy - Riko Aldi Febrianto; Adi S (Universitas Negeri Semarang, 2026)
Physical Education, Sports, and Health (PE) learning is not only oriented towards achieving physical abilities, but also towards forming meaningful learning experiences for students. One important psychological aspect that is influenced by these experiences is self-efficacy. This study aims to analyze the relationship between meaningful physical education and students' self-efficacy. The study uses a quantitative approach with a correlational design. The research sample consisted of 219 students from State Junior High School 2 Semarang, State Senior High School 12 Semarang, and State Vocational School 10 Semarang, selected using purposive sampling. The research instruments were a questionnaire on the meaning of physical education, which included the dimensions of enjoyment, challenge, competence, autonomy, and social interaction, and a questionnaire on student self-efficacy, both of which were presented on a Likert scale. Data analysis was performed using Spearman's correlation test because the data were not normally distributed. The results showed a positive and significant relationship between the meaning of physical education and student self-efficacy (r = 0.251; p < 0.05). This finding indicates that the more meaningful the PE learning is perceived by students, the higher their level of self-efficacy in participating in physical education activities. Thus, the application of meaningful physical education and self-efficacy principles is an important strategy in improving the quality of PE learning, which not only has an impact on physical aspects but also strengthens students' psychological aspects.